Development of an Automatic Mini-conveyor System for Product Monitoring - Joel Ewa Bassey; Katsina Christopher Bala; Nurudeen Abdul (Advanced Aspects of Engineering Research Vol. 9, 2021)
This chapter highlights the details in the development of an automatic mini-conveyor system for product monitoring. The design analysis was done in line with Fenner Dunlop conveyor belt design manual and other conveyor design manuals and electronic manuals and journals. It is a wireless-based monitoring, control, data acquisition system, MCDAS, enable immediate update of the detail of production line activities as the production runs are being initiated from one production shift to another. For every production run, information is gathered, therefore, with this system there is no downtime in data reporting and transmission and this data can be printed at the end of every production shift. And also has data log, where previous data can still be assessed. Therefore, with rapid advance in wireless information technologies, many solutions are emerging and its application in industries have been researched and developed. It can be concluded that this system which merges four technology that is; mini-conveyor, sensing and counting and signalling wireless network system into one solution is highly compatible and suitable to meet the requirement of any production line layout output monitoring system application in the manufacturing industries.